Oxford internationl primary Science student book 3 - Roberts, Deborah; Hudson, Terry; Haigh, Alan (China Oxford international primary, 2014)
The Oxford International Primary Science Student Book 3 (Second Edition) introduces young learners to fundamental scientific concepts through engaging and age-appropriate content. It covers key topics in biology, physics, and chemistry, with a focus on exploration and discovery. The book features vibrant illustrations, simple experiments, and interactive activities designed to spark curiosity and encourage hands-on learning. Each chapter includes clear explanations and opportunities for practical application, helping students build a solid foundation in science while developing critical thinking and observational skills.
Keywords: Science- Text Book